Production of Methane Gas by Ultrasonic Membrane System (UMAS) Using Palm Oil Mill Effluent (POME) as a Substrate - Wan Norain, Awang Long (2013)
This study is mainly focusing on methane production from palm oil mill effluent (POME) by using Ultrasonic Membrane Anaerobic System (UMAS). Design of anaerobic reactor was applied in order to design experimental work which is 100 mL volume digester of Ultrasonicated Membrane Anaerobic System (UMAS). The six kinetic parameters of UMAS such as COD, BOD, pH and TSS were studied. Reactor was operated under ambient temperature within the range ~30 to 35 ˚C. POME will be continuous up-flow feeding from the side flow into the anaerobic reactor and effluent samples will be taken from the reactor after 5 hours for analysis of the parameters at each batch of HRT. The start-up of the UMAS reactor was involved step increasing in influent organic volumetric loading rates from higher retention time to lower retention time of 392.16, 128.21, 119.05, 111.11, and 98.04 days. The acclimatization was done within 4 to 9 days to allow all the microorganisms present in the mixed liquor perfectly acclimatized to the new environmental. Mixture of methane and carbon dioxide gases produced was collected by using syringe. NaoH or KOH was filled in the syringe in order to adsorb the carbon dioxide from the methane gas. It is expected that the developed UMAS can be the effective process that has more excellent performance in methane production by encountering the membrane fouling hence decreased the retention time. Meanwhile, the five kinetic parameters listed such as COD content can be reduced up to 86% reduction from the original by complete treatment.